Influence of initial stresses on stress intensity factors at crack tips in a composite - Akbarov, SD; Yahnioglu, N; Turan, A (CONSULTANTS BUREAU, 2004)
The influence of initial tension or compression along cracks on the stress intensity factor (SIF) at crack tips under the action of additional normal forces on crack edges is studied for infinite bodies. A strip made of a composite material is considered. The strip ends are simply supported, and the strip contains a crack whose edges are parallel to its face planes. The strip is first stretched or compressed along crack edges, and then additional uniformly distributed normal forces are applied to the crack edges. The influence of the initial tension (compression) on the SIF caused by the additional normal forces is studied. The corresponding boundary-value problems are modelled with the use of the three-dimensional linearized theory of elasticity. All the investigations are carried out numerically by employing the finite-element method. The values of SIF are calculated by the energy release method.
Keywords: crack; stress intensity factor (SIF); composite; pretension; energy release rate; Mechanics; Materials Science; Polymer Science